The Enhancement Quality of Squalene As A Marine Chemopreventive Agent and Vitamin A Level in The Shark Liver Oil at The Territorial Ocean of Cilacap - Nurfauzi, Yuhansyah; Kurniawan, Wahyu; Tusrianto, . (Indonesian Journal of Cancer Chemoprevention, 2011)
Recently, shark liver oil is developed as mainstay product for the Cilacap fishermen proceed to be traditional supplementalfoods and health product that contains squalene and Vitamin A. Squalen is one of marine natural products has demonstratedproliferative activity in animal cancer studies and may havesome radioprotective effects.This observation is aimed to enhance and improve squalene acquirement quality organolepthically.This observation usesexperimental observation design.Shark liver in thebottle will be proceedby thetool that specially designed to produce shark liver oil. Its result is analyzed quantitatively togainthesqualeneandvitaminAlevel.Thecomparisonofsqualene level that has been produced in this observation isapproximately from 141 to 191 higher than standard squalene product in the market. The vitamin A level in thisobservation is approximately 3,6 higher than shark liver oilproduct in the market without processing by the observation tool. The technology in the observation uses heatingprinciple from perfect black tool that causes it more constantlyhot and causes oil flow out from shark liver organ.The oil in thebowl ofthe tool was filtered by zeolit,so that the unpleasantorfishy smell of the oil will decrease if compared with traditionalproduction process. Key words:Squalene,vitaminA,Sharkliveroil,Cilacap